Hinting Pali: Resolusi Konflik Masyarakat Adat Dayak Dalam Konflik Sengketa Tanah di Wilayah Kabupaten Katingan Kalimantan Tengah: Hinting Pali: Resolusi Konflik Masyarakat Adat Dayak Dalam Konflik Sengketa Tanah di Wilayah Kabupaten Katingan Kalimantan Tengah - Perdana, Dedy Ilham; Sadelman Tulis, Riamona; Adiwijaya, Saputra (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACT: Hinting Pali is an attempt to find a middle ground on land-based conflicts. Culture is often done when people who are involved in the dispute trying to find a way of peace with the traditional ceremony hinting pali. This research seeks to provide a new perspective on efforts to mitigate conflict within the community, with the cultural approach existing in an indigenous community in Tumbang Tanjung, Pulau Malan District, Central of Kalimantan Province. This study, in addition to finding the form or effort to minimize the conflict, also intends to provide a picture that the wealth of local communities in the deliberative conflict-related deliberation is still relevant in the current conditions. This research is expected to find a form of conflict resolution that is humanist without putting the efforts of violence vertically or horizontally.